2008
DOI: 10.1097/mao.0b013e31817ef49b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Complex Stapes Motion on the Response of the Cochlea

Abstract: The qualitative results provide supportive evidence that complex movements of the stapes footplate may lead to cochlear activity. Further experiments are necessary to confirm and quantify these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Several studies in human temporal bones have shown that the motion of stapes at high frequencies became more complex than the simple pistonlike motion at low frequencies (Chien et al 2006;Hato et al 2003;Heiland et al 1999). The complex motion of stapes at high frequencies was also reported in guinea pig (Huber et al 2008), cat, and gerbil ears (Decraemer et al 1999). Note that there was a measurement angle of 40-50°1 magnitude changes (with SD) between guinea pig ears with purulent effusion, 0.1 ml saline, and 0.2 ml saline.…”
Section: Effect Of Middle Ear Structural Changes On Tm Movementmentioning
confidence: 89%
“…Several studies in human temporal bones have shown that the motion of stapes at high frequencies became more complex than the simple pistonlike motion at low frequencies (Chien et al 2006;Hato et al 2003;Heiland et al 1999). The complex motion of stapes at high frequencies was also reported in guinea pig (Huber et al 2008), cat, and gerbil ears (Decraemer et al 1999). Note that there was a measurement angle of 40-50°1 magnitude changes (with SD) between guinea pig ears with purulent effusion, 0.1 ml saline, and 0.2 ml saline.…”
Section: Effect Of Middle Ear Structural Changes On Tm Movementmentioning
confidence: 89%
“…8). Such rocking motions are presumed to be caused by the stimuli parallel to the footplate, on the stapes head (excitations in the X H and Y H in Figure 10, Eiber et al 2007;Huber et al 2008).…”
Section: Rocking Motionsmentioning
confidence: 99%
“…On the measurement side, a previous study by de la Rochefoucauld et al (2008) reported that motion components other than the piston-like motion did not produce scala-vestibuli pressure in gerbil ears. However, a recent study by Huber et al (2008) showed that enhancement of the rocking motions of the stapes by mechanical stimulation affected the cochlear response in guinea pigs, as demonstrated by changes in compound action potentials (CAP). It is anticipated that there will be further investigation of the relation between the rocking motions and fluid-flux inside the cochlea, and methods to measure stapes motions, particularly the rocking motions, need to be systemically studied.…”
Section: Introductionmentioning
confidence: 99%
“…a fluid-jet flow, which, however, results in the generation of conventional travelling waves along the cochlear partition. In this sense, the cochlear excitation in our experiments on the RW stimulation is similar to excitation due to rocking movement of the stapes, which creates only local pressure gradients/fluid motion in the cochlea [37,38] resulting, nevertheless, in generation of the travelling waves and neural excitation [39,40]. In our experiments, the near-field pressure is proportional to the acceleration of the transducer which allows effective cochlear stimulation even at extremely small RW displacements at high frequencies.…”
Section: Discussionmentioning
confidence: 63%